Self‐Sorting Supramolecular Polymerization: Helical and Lamellar Aggregates of Tetra‐Bay‐Acyloxy Perylene Bisimide. (2nd August 2020) - Hecht, Markus; Leowanawat, Pawaret; Gerlach, Tabea; Stepanenko, Vladimir; Stolte, Matthias; Lehmann, Matthias; Würthner, Frank
Abstract: A new perylene bisimide (PBI), with a fluorescence quantum yield up to unity, self‐assembles into two polymorphic supramolecular polymers. This PBI bears four solubilizing acyloxy substituents at the bay positions and is unsubstituted at the imide position, thereby allowing hydrogen‐bond‐directed self‐assembly in nonpolar solvents. The formation of the polymorphs is controlled by the cooling rate of hot monomer solutions. They show distinctive absorption profiles and morphologies and can be isolated in different polymorphic liquid‐crystalline states. The interchromophoric arrangement causing the spectral features was elucidated, revealing the formation of columnar and lamellar phases, which are formed by either homo‐ or heterochiral self‐assembly, respectively, of the atropoenantiomeric PBIs. Kinetic studies reveal a narcissistic self‐sorting process upon fast cooling, and that the transformation into the heterochiral (racemic) sheetlike self‐assemblies proceeds by dissociation via the monomeric state. Abstract : Cool down : Depending on the cooling rate, a monomeric perylene bisimide equipped with four acyloxy bay substituents self‐assembles into two distinct polymorphs that exhibit distinctive optical properties and packing arrangements. The interchromophoric arrangement was elucidated in the liquid‐crystalline state, demonstrating the effect of homo‐ versus heterochiral self‐sorting, directing self‐assembly into one‐ and two‐dimensional structures, respectively.